Pengaruh Persistensi Laba, Konservatisme Akuntansi, Investment Opportunity Set dan Struktur Modal terhadap Kualitas Laba - Isa Mar’atus Syifa; Suwarno Suwarno (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to test the influence of earnings persistence, accounting conservatism, investment opportunity set and capital structure on earnings quality. The data source used in this research is secondary data using documentary data obtained from the official website of the Indonesian Stock Exchange. The sample used in this research was 88 data from property and real estate companies in 2019-2020 using purposive sampling. This research uses multiple linear regression analysis techniques. The regression results show that earnings persistence has a positive effect on earnings quality and investment opportunity set has a negative effect on earnings quality, while accounting conservatism and capital structure have no effect on earnings quality.